Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Pt. Bank Tabungan Negara (BTN) Cabang Ambon - Souhoka, Semuel (P3M Politeknik Negeri Ambon, 2024)
This research uses Training and Career Development as the independent variable, and Employee Performance as the dependent variable. The objectives of this research are 1). To determine the effect of job training on employee performance 2). To determine the effect of career development on employee performance 3). To determine the effect of job training and career development on the performance of employees of PT Bank Tabungan Negara (BTN) Ambon BranchThe sample used was employees of PT. State Savings Bank (BTN) Ambon Branch with a sample size of 40 respondents. The analysis used includes validity testing, reliability testing, model testing, multiple linear regression analysis and research hypotheses. Based on the research results, it can be seen that 1). Overall, the training and career development variables included in this research were proven to have a significant influence on employee performance at PT Bank Tabungan Negara (BTN) Ambon Branch. 2). Of the 2 (two) independent variables studied, the job training variable is the dominant variable that influences employee performance at PT Bank Tabungan Negara (BTN) Ambon Branch. 3). In this research, it is known that the variation in employee performance explained by training and career development is 61.5%, while 38.5% is explained by other variables not analyzed in the model. Keywords: Training, Development, Performance